Is it worth it? Patient and public views on the impact of their involvement in health research and its assessment: a UK-based qualitative interview study - Crocker, J; Boylan, A; Bostock, J; Locock, L (Wiley, 2016)
Background There are mounting calls for robust, critical evaluation of the impact of patient and public involvement (PPI) in health research. However, questions remain about how to assess its impact, and whether it should be assessed at all. The debate has thus far been dominated by professionals. Objective To explore the views of PPI contributors involved in health research regarding the impact of PPI on research, whether and how it should be assessed. Design Qualitative interview study. Setting and participants Thirty-eight PPI contributors involved in health research across the UK. Results Participants felt that PPI has a beneficial impact on health research. They described various impactful roles, which we conceptualize as the ‘expert in lived experience’, the ‘creative outsider’, the ‘free challenger’, the ‘bridger’, the ‘motivator’ and the ‘passive presence’. Participants generally supported assessing the impact of PPI, while acknowledging the challenges and concerns about the appropriateness and feasibility of measurement. They expressed a range of views about what impacts should be assessed, by whom and how. Individual feedback on impact was seen as an important driver of improved impact and motivation to stay involved. Conclusions While there appears to be widespread support for PPI impact assessment among PPI contributors, their views on what to assess and how are diverse. PPI contributors should be involved as equal partners in debates and decisions about these issues. Individual feedback on impact may increase PPI contributors’ potential impact and their motivation to stay involved.